THE CURRENT SITUATION OF THE QUALITY OF HEALTH INSURANCE MEDICAL EXAMINATION AND TREATMENT AT DISTRICT HOSPITALS IN THAI NGUYEN PROVINCE - ACCESS FROM THE PAID (Vietnam Journal of Community Medicine, 2022)
This study aims to analyze and evaluate the current situation of quality of medical examination and treatment by health insurance at district hospitals in Thai Nguyen province from the perspective of patients, thereby proposing some solutions to improve the quality of medical examination and treatment with Health Insurance at these hospitals in the period of 2022 -2026, contributing to improving patient satisfaction in order to reduce the burden on upper-level hospitals.
Keywords: Service quality, health insurance, medical examination and treatment by health insurance, hospitals, patients